Die Märtyrer von Nagrān und das Ende der Ḥimyar. Zur politischen Geschichte Südarabiens im frühen sechsten Jahrhundert - Nebes, Norbert (Aethiopica, 2008)
There is no other period within the pre-islamic history of Arabia providing such a number of different – literary and epigraphical – documents as the conflict between the ḥimyarites and the Abyssinians. In the 520s these struggles having also a strong religious-political connotation culminated in defeating and killing the South Arabian King Yūsuf (ḏū Nuwās) and the occupation of large parts of the Yemen by the Abyssinians, who were supported by the then great power Byzantium. Taking into consideration the current state of research the article gives a review of the course of events.